Pola Distribusi Hujan Kota Pekanbaru Berdasarkan Data Satelit TRMM Jaxa - Bunga Rafikah Zaki; Yohanna Lilis Handayani; Manyuk Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
One of parameters to determine the discharge is to know the pattern of rainfall distribution. To calculated the rainfall distribution is required hourly rainfall data of TRMM. Rainfall distribution patterns can be calculated using the empirical method of Alternating Block Method (ABM), Tadashi Tanimoto and Mononobe. The aim of this research to determine the pattern of rainfall distribution in the city of Pekanbaru from 2009 to 2016 based on the pattern and correlation. Based on shape, the most common TRMM distribution pattern is the bell shape that occurs from the duration of 3 to 9 hours and for the duration 2 hours has the form of a declining ladder. While based on correlation, pattern of rainfall distribution for duration of 3, 4, 6, and 7 hours tend to ABM Method, 5 hour duration tends to Mononobe Method and 8 hour duration tends to Tadashi Tanimoto Method. The results of this study have been compared with previous studies for Pekanbaru City, which of the two studies only rain with duration of 3 and 5 hours that have a match pattern.Keywords : The Pattern of rainfall distribution, Satellite rainfall data, Alternating Block Method (ABM), Modified Mononobe, Tadashi Tanimoto